2020
DOI: 10.1186/s13037-020-00238-6
|View full text |Cite
|
Sign up to set email alerts
|

The hidden risk of ionizing radiation in the operating room: a survey among 258 orthopaedic surgeons in Brazil

Abstract: Background: This study aims to assess orthopaedic surgeon knowledge in Brazil about ionizing radiation and its health implications on surgical teams and patients. Methods: A 15-question survey on theoretical and practical concepts of ionizing radiation was administered during the 23rd Brazilian Orthopaedic Trauma Association annual meeting. The survey addressed issues within orthopedic surgery, such as radiation safety concepts, protection, exposure, as well as the participant gender. Participants were either … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 17 publications
5
17
0
8
Order By: Relevance
“…This study is one of largest reported surveys undertaken to assess radiation safety knowledge and principles for orthopaedic surgeons. The findings are supported by other studies in the literature, [5][6][7][8][9][10][11][12][13][14][15][16][17] the majority of which were smaller local or regional surveys with less than 90 orthopaedic surgeon responses. [5][6][7][8][9][10][11] Overall, they showed limited radiation safety knowledge, lack of formalised training and poor usage of radiation protective equipment.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This study is one of largest reported surveys undertaken to assess radiation safety knowledge and principles for orthopaedic surgeons. The findings are supported by other studies in the literature, [5][6][7][8][9][10][11][12][13][14][15][16][17] the majority of which were smaller local or regional surveys with less than 90 orthopaedic surgeon responses. [5][6][7][8][9][10][11] Overall, they showed limited radiation safety knowledge, lack of formalised training and poor usage of radiation protective equipment.…”
Section: Discussionsupporting
confidence: 86%
“…A national survey of 258 Brazilian orthopaedic surgeons also concluded there was inadequate theoretical and practical knowledge regarding radiation exposure with only a minority using basic radiation protection equipment. 14 Fidan et al 15 (2019) analysed 180 surgeon's responses and highlighted lack of radiation safety knowledge with only 12% having received training. Interestingly, only 68% wore lead aprons and 52% To our knowledge, this study is the largest European survey in terms of total responses and one of the largest reported internationally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study as observed in table 5 most of the respondents (83.67%) are aware of the harmful effects of radiation: Surgeons (100%), Anesthesiologists (60%), Theatre Nurses (66%) and Radiographers (100%). This awareness rate is high when compared to that found among a group of theatre team in Brazil (55.4%) (Pires et al, 2020). Though the respondents are aware of the harmful effects of radiation, the study however shows that they have an average level of awareness to radiation protection or safety measures with exception of Radiographers: Surgeons (58.8%), Anesthesiologists (50%), Theatre Nurses (33.3%), and Radiographers (100%).…”
Section: Resultsmentioning
confidence: 66%